The Impact of Psychological Flexibility on Psychological Well-Being in Adults With Obesity - Guerrini Usubini, Anna; Varallo, Giorgia; Granese, Valentina; Cattivelli, Roberto; Consoli, Simone; Bastoni, Ilaria; Volpi, Clarissa; Castelnuovo, Gianluca; Molinari, Enrico (Frontiers in Psychology, 2021)
Obesity is a global health problem that affects both physical and psychological health and well-being. Psychological flexibility is one of the key components related to psychological health. This cross-sectional study aims to investigate the impact of psychological flexibility on psychological well-being in a sample of 220 individuals with obesity. Multivariate analysis was performed to investigate the role of psychological flexibility in explaining psychological well-being, controlling for confounding factors (sex, age, and Body Mass Index). According to the results, psychological flexibility significantly explained psychological well-being. Our study provides additional evidence of the impact of psychological flexibility on psychological well-being. It also provides further support for the importance of integrating psychological flexibility in the psychological interventions for obesity.